Transactions on Computational Collective Intelligence XV - Nguyen, Ngoc Thanh.; Nguyen, Ngoc Thanh.; Kowalczyk, Ryszard.; Kowalczyk, Ryszard.; Corchado, Juan Manuel.; Corchado, Juan Manuel.; Bajo, Javier.; Bajo, Javier. (Transactions on Computational Collective Intelligence, 2014)
These transactions publish research in computer-based methods of computational collective intelligence (CCI) and their applications in a wide range of fields such as the Semantic Web, social networks, and multi-agent systems. TCCI strives to cover new methodological, theoretical and practical aspects of CCI understood as the form of intelligence that emerges from the collaboration and competition of many individuals (artificial and/or natural). The application of multiple computational intelligence technologies, such as fuzzy systems, evolutionary computation, neural systems, consensus theory, etc., aims to support human and other collective intelligence and to create new forms of CCI in natural and/or artificial systems. This 15special issue is dedicated to the International Conference on Practical Applications on Agents and Multi-Agent Systems (PAAMS 2012 and PAAMS 2013) held in Salamanca, Spain.